Concept of habitual residence through selected sources of EU Private international law and jurisprudence of the Court of Justice of the European Union: functional approach vs. strict textualism - Dragišić, Radmila (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
In this paper, through content analysis and comparative analysis, we consider the concept of habitual residence, which is an important connecting factor of contemporary EU Private international law. Concept of habitual residence is considered through selected sources of EU private international law and the jurisprudence of the Court of Justice of the European Union. Inevitably it is refered to the regulations of Rome I and Rome II, which produce a content determination of the habitual residence of legal and natural persons (which performing economic activity) and which, unlike sources of law in the field of personal statute, did not leave the concept of habitual residence indefinite. We point out the importance of recitals in the corpus of the acquis, which, as part of the preamble of the sources of EU law, gives basic instructions for the Court of Justice when providing guidance to national courts on criteria for determining what is to be considered a habitual residence in different situations. Also, we pointed out the positions established by the Court of Justice in its judgments in cases C-80/19 and C-289/20, regarding the possibility of disposing of multiple habitual residences, as well as the position taken in the judgment of 27 April 2016 in case C -528/14 on the question of whether a natural person can simultaneously have a habitual residence in a Member State of the Union and in a third country. At the end, we bring key considerations.
Keywords: European Union; habitual residence; acquis; jurisprudence; Court of Justice of the EU; national courts; autonomous content determination